Rekayasa Sistem Informasi Retribusi Sampah Berbasis Web untuk Optimalisasi Kinerja Bidang Pengelolaan Sampah - Hilyah Magdalena; Hadi Santoso; Karina Rochmayani (CogITo Smart Journal, 2019)
Managing municipal waste efficiently is a challenge in itself. Waste levies as a source of regional revenue need to be managed optimally so that the waste transportation services for the community can run smoothly. Constraints faced by the City Government of Pangkalpinang are how to anticipate the limited number of garbage lift fleets, the increasing population density, and the manual administration system. To improve the quality of waste transportation services, one of them is by upgrading from manual to a web-based system with the aim of making it easier to manage fleet transport schedules, making it easier for people to pay waste fees, and making it easier to report waste levies. The system will be built using the Object Oriented Analysis and Design (OOAD) methodology because with OOAD the system can be developed gradually and continuously. This web-based levy information system is also expected to be able to facilitate public access to cleaning services